Related Factors to Choose Cesarean Rather than Normal Delivery among Shirazian Pregnant Women - Majid Movahed; Halimeh Enayat; Esfandiar Ghaffarinasab; Sedigheh Alborzi; Rohollah Mozafari (Fasa University of Medical Sciences, 2012)
Background & objective: Although delivering with Cesarean method is preferred in limited cases which has dangerous effects on child or mother's health, rate of cesarean is increasing vastly nowadays. The main purpose of this study was to explore Social, Cultural and Demographic factors related to this phenomenon among pregnant women of Shiraz. Materials & Methods: In this study 600 pregnant women residing in Shiraz were selected using Lin cross size of sample (multistage sampling). Data were collected through the validated questionnaire and analyzed with SPSS software by multi-variables logistic regression and X2 techniques. Results: Research hypotheses about significant relation among these factors (age, age of marriage, education, spouse's education, occupational status, place of birth, social class status, previous childbirth method, record of barrenness, place of previous childbirth, place of pregnant care, record of cesarean in family and attitude toward cesarean) with choice of cesarean have been approved. Research hypotheses about month of pregnancy, number of pregnancy and knowledge of delivery method and cesarean have been rejected. Conclusion: Due to significant positive attitude of women's towards the cesarean, rather than normal delivery, it is necessary to inform them about the advantages of normal delivery and health hazard which might cause by Cesarean to the mother and child. The change of women's attitude about cesarean is needed to avoid further complication.